The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3177/jnsv.51.329
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Intake May Negatively Correlate with Energy Intake in Human: A Cross-Sectional Study in Japanese Female Students Aged 18 Years

Abstract: SummaryL-Histidine (histidine), a precursor of neuronal histamine, has recently been hypothesized to suppress food intake. The association between dietary histidine and energy intake was examined among 1,689 Japanese female students of dietetic courses aged 18y. Nutrient intakes were assessed over a 1-mo period with a validated, self-administered, diet history questionnaire. Both intake of histidine and the ratio of histidine to protein (histidine/ protein) statistically and positively correlated with energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…acid metabolism disorder and inflammation and/or oxidative stress, which suggests that more attention has to be paid to uncovering amino acid metabolism in obese individuals in a further study. In addition, previous studies have shown that women are more sensitive to dietary histidine and energy intake than men (42,43) . Therefore, we chose female rats as the experimental animals in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…acid metabolism disorder and inflammation and/or oxidative stress, which suggests that more attention has to be paid to uncovering amino acid metabolism in obese individuals in a further study. In addition, previous studies have shown that women are more sensitive to dietary histidine and energy intake than men (42,43) . Therefore, we chose female rats as the experimental animals in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Because previous studies found that women were more sensitive to dietary histidine and energy intake than men [14,36], we chose women to participate in our study. Therefore, the findings may not be generalised to the total population.…”
Section: Discussionmentioning
confidence: 99%
“…According to the histidine intake and supplementation described in previous studies [13][14][15][16], we recruited 20 obese female university students for the pilot experiment, randomly assigned into two groups: ten women took two 1 g histidine tablets after breakfast and two tablets after dinner (4 g/day histidine) and the other ten women took four tablets after breakfast and four tablets after dinner (8 g/day histidine) for 2 weeks. During the supplementation period, no side effects were reported and serum superoxide dismutase (SOD) was increased in both groups at the secondweek (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Daily HIS intake correlated inversely with energy intake. [119] Internet-based cross-sectional study in a Chinese population (n = 88).…”
Section: Decrease In Fasting Plasma Glucose Levelsmentioning
confidence: 99%